Influence of school leadership, discipline, and work motivation toward high school teacher performance - Setiyaningsih, Theresia Titik (Harmoni Sosial: Jurnal Pendidikan IPS, 2020)
The research aims to reveal the effect of 1.) Principal leadership; 2.) Teacher’s work discipline; 3.) Teacher’s work motivation; 4.) Principal leadership; 5.) Teacher’s work discipline; and 6.) Teacher’s work motivation simultaneously on the performance of the teachers of state senior high schools in Kulonprogo Regency. The research was ex-post facto research with the quantitative approach. The sampling technique used was a proportional stratified random sampling of the population of 385 teachers in the Kulonprogo Regency. Moreover, the sampling as much as 196 teachers are in Kulonprogo Regency. The validation is done through expert judgment and confirmatory factor analysis (CFA). The reliability was measured using Cronbach’s Alpha (Î±). The data analysis used the Chi-Square statistical technique. The results are as follows: 1.) The principal leadership affects the performance of the teachers; 2.) The teacher’s work discipline; 3.) The work motivation affects their performance; 4.) The principal leadership, teacher’s work discipline; and 5.) Teacher’s work motivation simultaneously on the performance of the teachers. The useful contribution of each variable is as follows: 1.) Principal leadership is 44,5%; 2.) Teacher’s work discipline is 66,6%; and 3.) teacher’s work motivation is 64,3%. It means that principal leadership, teacher’s work discipline, and teacher’s work motivation affect teacher performance partially and simultaneously.